1969
DOI: 10.1016/s0006-3495(69)86414-3
|View full text |Cite
|
Sign up to set email alerts
|

Electroosmosis in Membranes: Effects of Unstirred Layers and Transport Numbers

Abstract: In an earlier paper, it was shown that the differences in transport numbers in membranes and adjacent solutions will result in a depletion and enhancement of the local concentration profiles at the appropriate interfaces. These should, in general, cause both current-induced volume flows and transient changes in membrane potential difference (PD). The predicted concentration changes were measured near an isolated segment of plant cell wall just after a current pulse. The current-induced volume flows observed we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
65
0

Year Published

1972
1972
1995
1995

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(69 citation statements)
references
References 7 publications
4
65
0
Order By: Relevance
“…(Barry & Hope, 1969a). This suggestion seems reasonable, because the size of the three changes was directly related to the time integral of the current (see Fig.…”
Section: I-90omentioning
confidence: 79%
“…(Barry & Hope, 1969a). This suggestion seems reasonable, because the size of the three changes was directly related to the time integral of the current (see Fig.…”
Section: I-90omentioning
confidence: 79%
“…(51). Thus, the possi bility exists that the "sweeping-away" effect of osmotic water flow in the lateral intercellular spaces reduced the salt concentration and accordingly, the osmotic pressure gradient across the luminal interfaces (23,(32)(33)(34)(35)66 is the diffusional resistance (aII/Di') of the unstirred layer. Equation 11 indicates that Claii will be reduced in exponential relationship to both Jw and Rei.…”
Section: Resultsmentioning
confidence: 99%
“…Second, recent observations in our laboratory indicate that, in certain instances, osmotic flow-dependent changes in the concentration profiles of solutes at the interfaces between unstirred layers and membranes, rather than the solvent drag phenomenon, may account for changes in the fluxes of solutes across membranes during osmosis (31). Similarly, apparent electrokinetic phenomena in plant cells (32,33), gall bladder (34,35), and squid axon (36) may be referable, in part, to perturbations produced by volume flow in the ionic composition of unstirred layers at the membrane interfaces rather than to coupling of ionic and volume flows within membranes. On the basis of such observations, we are skeptical about analyses of water flux data which do not consider explicitly the effects of unstirred layers on transport processes.…”
Section: Introductionmentioning
confidence: 92%
“…However, the interpretation of the results of such experiments is complicated by the fact that electrodiffusion of ions (mainly Na+ toward the cathode and Cl-toward the anode) across a membrane of selective permeability, such as the tracheal epithelium, inevitably creates an osmotic gradient in the unstirred layers adjacent to the membrane. This osmotic gradient in turn results from the transport number effect, a phenomenon which was demonstrated by Barry & Hope (1969). Thus, an osmotic Jv would occur, which would tend to obscure the purely electrically induced Jv and might invalidate this approach.…”
Section: Discussionmentioning
confidence: 99%
“…Yet this view is not universally accepted (Hill, 1975a) and other mechanisms, such as electrokinetic coupling between water and ions migrating across cells down the membrane potential (Hill, 1975b), or a fluid pump (Eldrup, Frederiksen, Mollgard & Rostgaard, 1982) have been suggested. However it was reported that, in leaky epithelia, the putative electrokinetic Jv, induced by an external electrical gradient, resulted mainly from an osmotic force built up in unstirred layers adjacent to the epithelial cells by the transport number effect, rather than from a direct coupling between water and ionic current (Barry & Hope, 1969;Wedner & Diamond, 1969).…”
Section: Introductionmentioning
confidence: 99%